Global ecological, social and economic impacts of marine plastic - Beaumont, Nicola J.; Aanesen, Margrethe; Austen, Melanie C.; Börger, Tobias; Clark, James R.; Cole, Matthew; Hooper, Tara; Lindeque, Penelope K.; Pascoe, Christine; Wyles, Kayleigh J. (Marine pollution bulletin, 2019)
This research takes a holistic approach to considering the consequences of marine plastic pollution. A semi-systematic literature review of 1191 data points provides the basis to determine the global ecological, social and economic impacts. An ecosystem impact analysis demonstrates that there is global evidence of impact with medium to high frequency on all subjects, with a medium to high degree of irreversibility. A novel translation of these ecological impacts into ecosystem service impacts provides evidence that all ecosystem services are impacted to some extent by the presence of marine plastic, with a reduction in provision predicted for all except one. This reduction in ecosystem service provision is evidenced to have implications for human health and wellbeing, linked particularly to fisheries, heritage and charismatic species, and recreation. •Marine plastic has a global impact on all ecological subjects reviewed.•There are negative impacts on the provision of almost all marine ecosystem services.•Negative human wellbeing impacts, particularly fisheries, heritage, recreation.•Economic costs conjectured: $3300–$33,000 per tonne of marine plastic per year.